2017
DOI: 10.1002/ange.201707872
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Reactive Oxoiron(IV) Complex Supported by a Bioinspired N3O Macrocyclic Ligand

Abstract: The sluggish oxidants [FeIV(O)(TMC)(CH3CN)]2+ (TMC=1,4,8,11‐tetramethyl‐1,4,8,11‐tetraazacyclotetradecane) and [FeIV(O)(TMCN‐d12)(OTf)]+ (TMCN‐d12=1,4,7,11‐tetra(methyl‐d3)‐1,4,7,11‐tetraazacyclotetradecane) are transformed into the highly reactive oxidant [FeIV(O)(TMCO)(OTf)]+ (1; TMCO=4,8,12‐trimethyl‐1‐oxa‐4,8,12‐triazacyclotetradecane) upon replacement of an NMe donor in the TMC and TMCN ligands by an O atom. A rate enhancement of five to six orders of magnitude in both H atom and O atom transfer reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The breakthrough in the preparation of synthetic Fe IV –oxido complexes came from the laboratories of Nam and Que, who reported the first crystallographically characterized Fe IV –oxido complex in [Fe IV (O)­(TMC)­(MeCN)] 2+ (TMC = tetramethylcyclam and MeCN = acetonitrile; Figure A) and later followed that with the structure of [Fe IV (O)­(N4Py)] 2+ (N4Py = N , N -bis­(2-pyridylmethyl)- N -bis­(2-pyridyl)­methylamine; Figure B). , The structural analyses of these complexes showed relatively short Fe–O bond lengths of 1.646(3) and 1.636(3) Å, which are indicative of Fe IV –oxido species. There have been numerous spectroscopic and computational studies on these complexes that corroborate their assignments as Fe IV species, but they both have spin ground states of S = 1, which differ from those found in proteins. ,, Nevertheless, these complexes serve as important contributions to the field, and there is now a library of over 100 examples of S = 1 Fe IV –oxido complexes in similar ligand frameworks. They have been particularly useful in delineating the properties of the electronic structure and demonstrating how optical spectroscopy is a reliable spectroscopic handle for Fe IV –oxido complexes. The signature features of synthetic mononuclear Fe IV –oxido species are weak bands around 700–900 nm that are assigned to a d–d transition. , The energy of the d–d transition is sensitive to the primary coordination sphere around the Fe IV –oxido unit, to both the equatorial ligands within the N–ligand frameworks and the exogenous ligand trans to the oxido ligand. , …”
Section: Nonheme Feivo Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakthrough in the preparation of synthetic Fe IV –oxido complexes came from the laboratories of Nam and Que, who reported the first crystallographically characterized Fe IV –oxido complex in [Fe IV (O)­(TMC)­(MeCN)] 2+ (TMC = tetramethylcyclam and MeCN = acetonitrile; Figure A) and later followed that with the structure of [Fe IV (O)­(N4Py)] 2+ (N4Py = N , N -bis­(2-pyridylmethyl)- N -bis­(2-pyridyl)­methylamine; Figure B). , The structural analyses of these complexes showed relatively short Fe–O bond lengths of 1.646(3) and 1.636(3) Å, which are indicative of Fe IV –oxido species. There have been numerous spectroscopic and computational studies on these complexes that corroborate their assignments as Fe IV species, but they both have spin ground states of S = 1, which differ from those found in proteins. ,, Nevertheless, these complexes serve as important contributions to the field, and there is now a library of over 100 examples of S = 1 Fe IV –oxido complexes in similar ligand frameworks. They have been particularly useful in delineating the properties of the electronic structure and demonstrating how optical spectroscopy is a reliable spectroscopic handle for Fe IV –oxido complexes. The signature features of synthetic mononuclear Fe IV –oxido species are weak bands around 700–900 nm that are assigned to a d–d transition. , The energy of the d–d transition is sensitive to the primary coordination sphere around the Fe IV –oxido unit, to both the equatorial ligands within the N–ligand frameworks and the exogenous ligand trans to the oxido ligand. , …”
Section: Nonheme Feivo Speciesmentioning
confidence: 99%
“…The literature indicates that CPET pathways are the most common for reactions involving Fe IV O complexes and substrates with a C–H bond. This conclusion comes from numerous studies with synthetic Fe IV O species that show strong correlations between log­( k 2 ) and BDFE C–H of the substrates (where k 2 is the second-order rate constant of a reaction). ,,,,, Linear free-energy relationships of this type follow from the Bell–Evans–Poyanyi (BEP) principle, , which predicts that experimentally obtained rate constants increase with either a decrease in BDFE C–H of the substrate or an increase in energy released from formation of the MO–H bond (that is, BDFE O–H ). These BDFE O–H values, however, are missing from the literature; although there are reports for some systems, there are still too few examples that are derived from experiments.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Component K1 has an isomer shift δ =0.19 mm s −1 and a quadrupole splitting Δ E Q =1.38 mm s −1 . Isomer shifts in the range of 0.14–0.17 mm s −1 are typical for non‐heme iron(IV) oxo species in solution . The Mössbauer spectrum of solid polycrystalline 2 shows δ =0.19 mm s −1 , which is (given the experimental error of ±0.03 mm s −1 ) the same as that of complex 1 ( δ =0.17(1) mm s −1 ) .…”
Section: Figurementioning
confidence: 69%
“…47 On the other hand, the substitution of the N-methyl groups in the tetramethylcyclam scaffold with oxygen atoms resulted in a rate enhancement for hydrogen atom abstraction (HAT) and oxygen atom transfer (OAT) by 5 to 6 orders of magnitude as compared to its parent complex. 57 It was suggested that the rate enhancement may be due to the higher electrophilicity of the iron center as a result of the equatorial oxygen atoms as compared to N-methyl groups. Recently, Kaur and Mandal reported a thorough computational study on the role of equatorial sulfur substitution in the C−H activation reactivity of iron(IV)− oxo cyclam complexes.…”
Section: ■ Introductionmentioning
confidence: 99%